Domestic Institutions and Credible Signals1 - Uzonyi, Gary; Souva, Mark; Golder, Sona N (International studies quarterly, 2012)
Uzonyi, Gary, Mark Souva, and Sona N. Golder. (2012) Domestic Institutions and Credible Signals. International Studies Quarterly, doi: 10.1111/j.1468‐2478.2012.00746.x  © 2012 International Studies AssociationAudience costs are a central feature of many prominent theories of international conflict. We advance the understanding of audience costs by specifying the domestic institutions necessary to generate them. In our conceptualization, audience cost capacity (ACC) is a function of the availability of alternative rulers and the cost of mobilizing against the incumbent. This conceptualization leads to the first measure of ACC that has variation between more and less democratic political systems and variation within autocracies. We subject our measure to a rigorous set of tests that includes addressing selection effects and temporal treatment effects, neither of which have been fully examined in this research area. The empirical analysis offers strong support for the validity of our measure.